2021
DOI: 10.12998/wjcc.v9.i30.9070
|View full text |Cite
|
Sign up to set email alerts
|

Serum calcium, albumin, globulin and matrix metalloproteinase-9 levels in acute cerebral infarction patients

Abstract: BACKGROUND Hemorrhagic transformation (HT) is a common complication in patients with cerebral infarction. However, its pathogenesis is poorly understood. The knowledge of factors that may increase risk for HT may help in improving the safety of thrombolytic therapy. AIM To investigate the predictive value of serum calcium, albumin, globulin and matrix metalloproteinase-9 (MMP-9) levels for HT after intravenous thrombolysis (IVT) in patients with acute cerebral infarctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…An increase in globulin level is an independent risk factor for HT has been illustrated in patients receiving intra-arterial thrombolysis (Xing et al, 2014). Moreover, Zhong et al (2021) recently reported that the globulin level was also a risk factor for HT in patients with AIS after IVT. However, they measured globulin levels before thrombolysis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…An increase in globulin level is an independent risk factor for HT has been illustrated in patients receiving intra-arterial thrombolysis (Xing et al, 2014). Moreover, Zhong et al (2021) recently reported that the globulin level was also a risk factor for HT in patients with AIS after IVT. However, they measured globulin levels before thrombolysis.…”
Section: Discussionmentioning
confidence: 96%
“…Besides, serum globulin levels have been used to assess the severity of chronic inflammation (Wu et al, 2019). Some studies have found that globulin level was a risk factor for HT after IVT in patients with AIS (Zhong et al, 2021). However, no study has investigated the association between ALP and globulin levels and the long-term clinical outcomes after intravenous thrombolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Albumin has been shown to have antioxidant, anti-inflammation, and anti-apoptosis in endothelial cells effects ( 25 ). Previous studies have shown that the decrease in albumin level or increase in globulin level might be associated with post-thrombolysis HT in ischemic stroke patients ( 26 , 27 ). Our study also showed that serum AGR ( P < 0.001) was related to post-thrombolysis HT in univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This study also found that leukocytes might serve a mediating effect between A/G and SAP, which further confirmed that inflammatory mechanisms might play an essential role between A/G and SAP. A third possibility is that high levels of albumin and low levels of globulin have neuroprotective effects, which may influence the risk of SAP by detoxifying endogenous and exogenous molecules, maintaining the integrity of the blood-brain barrier, increasing hypoxia tolerance, decreasing brain edema, and modulating neural apoptosis and inflammation reactions (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%